2021
DOI: 10.31489/2021bmg4/60-70
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphisms characteristic

Abstract: The article presents the characteristics of the main vitamin D receptor (VDR) gene polymorphisms: rs2228570 (FokI), rs731236 (TaqI), rs1544410 (BsmI) and rs7975232 (ApaI). The role of the vitamin D hormonally active form (1,25(OH)2D3, calcitriol) as a transcription factor regulating gene expression in target cells by binding to the vitamin D receptor protein is described. The immunomodulatory and mediating effect of VDRs on the biological functions of the human body has been noted. A description of the vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Previously, in review article, we compared rs2228570 frequency alleles and genotypes submitted in dbSNP NCBI (National Center for Biotechnology Information, USA) with data published in peer-reviewed publications [15]. It was found that rs2228570 is four-allelic, with a predominance of G (0.611257) and A (0.388743) alleles [16].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, in review article, we compared rs2228570 frequency alleles and genotypes submitted in dbSNP NCBI (National Center for Biotechnology Information, USA) with data published in peer-reviewed publications [15]. It was found that rs2228570 is four-allelic, with a predominance of G (0.611257) and A (0.388743) alleles [16].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, a higher rate of ApaI (50%), BsmI (68.40%), FokI (60%), and TaqI (91.40%) polymorphisms was observed in Iran ( 30 ), Indonesia ( 48 ), Iran ( 29 ), and China ( 50 ). In the study of Protas et al in 2023, it was shown that the VDR polymorphism frequency may depend on ethnicity ( 69 ). The TB report of the World Health Organization (WHO) has shown that the yellow-skinned race is more susceptible to TB than the black and white-skinned race.…”
Section: Discussionmentioning
confidence: 99%